2020
DOI: 10.1016/j.mayocpiqo.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Febuxostat on Mortality and Cardiovascular Outcomes

Abstract: Objective: To investigate the association between using febuxostat and cardiovascular events. Methods: Systematic search of randomized controlled trials was performed using PubMed/MEDLINE, Cochrane review, and EMBASE databases through April 17, 2019. Meta-analysis was performed using random effect model and estimates were reported as risk difference (RD) with 95% CIs. The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation approach. The main outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A systematic review and meta-analysis of Mayo Clinic included 15 RCTs including more than 100,000 patients with gout and hyperuricemia and showed that there was no significant risk of cardiovascular events including mortality with febuxostat compared with controls. 41 The last included study was in 2019, therefore not including the FAST trial. Like previously published systematic reviews and meta-analyses on the cardiovascular safety of febuxostat compared with allopurinol, the authors included MACE forest plot studies where MACE was neither defined nor its components mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review and meta-analysis of Mayo Clinic included 15 RCTs including more than 100,000 patients with gout and hyperuricemia and showed that there was no significant risk of cardiovascular events including mortality with febuxostat compared with controls. 41 The last included study was in 2019, therefore not including the FAST trial. Like previously published systematic reviews and meta-analyses on the cardiovascular safety of febuxostat compared with allopurinol, the authors included MACE forest plot studies where MACE was neither defined nor its components mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Like previously published systematic reviews and meta-analyses on the cardiovascular safety of febuxostat compared with allopurinol, the authors included MACE forest plot studies where MACE was neither defined nor its components mentioned. [41][42][43] This could result in underestimation or overestimation of results and misinterpretation of the cardiovascular safety of febuxostat. In addition, Gao colleagues 44 published a systematic review and meta-analysis in 2021 on trials including retrospective, cohort, and observational studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 In November 2017, the FDA put a boxed warning to clinicians and patients due to the increased risk of cardiovascular complications and deaths by this drug. 37,38 Topiroxostat was approved in June 2013 as a xanthine oxidase inhibitor for the management of gout and hyperuricemia. 39 It also causes gouty arthritis and liver dysfunction like effects.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%